2013
DOI: 10.5966/sctm.2013-0125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human Adipose-Derived Stem Cells Isolated from Subcutaneous, Omental, and Intrathoracic Adipose Tissue Depots for Regenerative Applications

Abstract: A broader understanding was sought regarding the influence of specific adipose tissue depots on the isolated adipose‐derived stem cell (ASC) populations through a systematic comparison of donor‐matched abdominal subcutaneous fat and omentum, and donor‐matched pericardial adipose tissue and thymic remnant samples. Results suggest that depot selection is an important factor to consider when applying ASCs in tissue‐specific cell‐based regenerative therapies, and also highlight pericardial adipose tissue as a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 78 publications
9
99
3
Order By: Relevance
“…ADSCs are a type of mesenchymal stem cell (MSC) present within adipose tissue, which have a strong proliferative capacity, multiple differentiation potential, and low immune rejection response (6,94). ADSCs can be induced to differentiate into multiple lineages, such as cartilage, bone, fat, nerve, muscle, and other cells (121).…”
Section: Adscsmentioning
confidence: 99%
“…ADSCs are a type of mesenchymal stem cell (MSC) present within adipose tissue, which have a strong proliferative capacity, multiple differentiation potential, and low immune rejection response (6,94). ADSCs can be induced to differentiate into multiple lineages, such as cartilage, bone, fat, nerve, muscle, and other cells (121).…”
Section: Adscsmentioning
confidence: 99%
“…For instance, ADSC isolated from intrathoracic depots exhibited a longer average doubling time and a higher proportion of CD34 + cells compared with those isolated from subcutaneous fat or the omentum. Moreover, subcutaneous and pericardial adipose tissue yielded ADSC with enhanced adipogenic differentiation potential, while ADSC from the omentum displayed high levels of osteogenic markers (Russo et al 2014). Another study that underscores the importance of the origins of ADSC from a therapeutic point of view is its finding that adipose tissues of slightly different origins in close vicinity (i.e., epicardial fat, pericardial fat, and the right atrium) exhibited significantly different capacities of secreting trophic and inflammatory cytokines, different degrees of upregulation of inflammation-and fibrosis-related genes, as well as different therapeutic effects in a rat model of myocardial infarction to which mesenchymal stem cells from right atrium and epicardial fat were even found to be detrimental (Naftali-Shani et al 2013).…”
Section: Source-and Donor-dependent Variability In Adsc Qualitymentioning
confidence: 99%
“…As a result, although subcutaneous adipose tissue especially that from the abdomen, thigh, and buttock removed through fat-extracting body-shaping procedures such as liposuction and lipectomy (Chia and Theodorou 2012) used to be regarded as medical waste products, it now serves as a readily available clinical source of adipose-derived stem cells. On the issue of the optimal source of ADSC, a previous clinically-oriented study comparing the properties of ADSC isolated from human adipose tissues of different depots, including abdominal subcutaneous fat, omentum, pericardial adipose tissue, and thymic remnants, has demonstrated that ADSC isolated from different sources exhibited varied proliferation and differentiation capacities that should be taken into account to serve a specific therapeutic purpose (Russo et al 2014). For instance, ADSC isolated from intrathoracic depots exhibited a longer average doubling time and a higher proportion of CD34 + cells compared with those isolated from subcutaneous fat or the omentum.…”
Section: Source-and Donor-dependent Variability In Adsc Qualitymentioning
confidence: 99%
“…The depot-specific differences in ASC has been studied in multiple models [8,73] . For example, rat ASC from the neck show lower rates of proliferation than other sources [8] .…”
Section: Profile and Identitymentioning
confidence: 99%